2019
DOI: 10.1108/rbf-06-2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

Predictable patterns following large price changes and volume

Abstract: Purpose The purpose of this paper is to examine the short horizon stock behavior following large price shocks in the Indian stock market. Design/methodology/approach The author followed the methodology developed by Pritamani and Singhal (2001) to the short horizon stock behavior following large price shocks. Multivariate regression has also been used to test the robustness of the evidenced results. Findings The abnormal return following large one-day price changes were not found to be important. However, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…They also showed that the risk-based explanations could not explain the evidenced reversals. Parthasarathy (2019) examined the reversal patterns following large price shocks using raw daily returns as the trigger and found support for the behavioural explanations. The study found that large price changes accompanied by low volume exhibited significant reversals over the following 20-day period and suggested significant economic profits.…”
Section: Review Of Literaturementioning
confidence: 97%
See 1 more Smart Citation
“…They also showed that the risk-based explanations could not explain the evidenced reversals. Parthasarathy (2019) examined the reversal patterns following large price shocks using raw daily returns as the trigger and found support for the behavioural explanations. The study found that large price changes accompanied by low volume exhibited significant reversals over the following 20-day period and suggested significant economic profits.…”
Section: Review Of Literaturementioning
confidence: 97%
“…Bremer and Sweeney (1991) used a novel approach, where stock returns exceeding a trigger value were included in the sample, unlike the earlier approach of ranking stocks based on their past returns. This approach was followed by Pritamani and Singhal (2001), Benou and Richie (2003), Himmelmann et al (2012) and Parthasarathy (2019).…”
Section: Review Of Literaturementioning
confidence: 99%